Economic Factors Influencing the Abolition of Slavery in the British Empire - David Jones (European Journal of Historical Research, 2024)
Purpose: The aim of the study was to assess the economic factors influencing the abolition of slavery in the British empire. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that the shift from an agrarian to an industrial economy reduced the reliance on slave labor, as mechanized production in factories became more efficient and cost-effective than manual labor on plantations. Additionally, the rise of free labor markets and wage labor provided a more flexible and scalable workforce that aligned better with the burgeoning industrial economy. Another critical economic factor was the decline in profitability of the sugar colonies. Intense competition from other sugar-producing regions, coupled with fluctuating sugar prices, made slave-based plantation economies less lucrative. As profits dwindled, the economic justification for maintaining slavery weakened. Furthermore, the growing influence of abolitionist movements, which highlighted the moral and ethical issues surrounding slavery, began to sway public opinion and policymakers. These movements also demonstrated that free labor could be more productive and sustainable in the long run. Implications to Theory, Practice and Policy: Capitalism and free market theory, labor economics and human capital theory and global trade and comparative advantage theory may be used to anchor future studies on assessing the economic factors influencing the abolition of slavery in the British empire. Practical implications suggest that contemporary debates on labor rights and ethical business practices can draw lessons from historical abolitionist movements. Policymakers can benefit from historical analyses of economic influences on abolition by considering the economic incentives and disincentives that drove historical policy changes.